Relevance Function of Linc-ROR in the Pathogenesis of Cancer - Chen, Wenjian; Yang, Junfa; Fang, Hui; Li, Lei; Sun, Jun (Frontiers in Cell and Developmental Biology, 2020)
Long noncoding RNAs (lncRNAs) are the key components of noncoding RNAs (ncRNAs) with a length of 200 nucleotides. They are transcribed from the so-called "dark matter" of the genome. Increasing evidence have shown that lncRNAs play an important role in the pathophysiology of human diseases, particularly in the development and progression of tumors. Linc-ROR, as a new intergenic non-protein coding RNA, has been considered to be a pivotal regulatory factor that affects the occurrence and development of human tumors, including breast cancer (BC), colorectal cancer (CRC), pancreatic cancer (PC), hepatocellular carcinoma (HCC) and so on. Dysregulation of linc-ROR has been closely related to advanced clinicopathological factors predicting a poor prognosis. As linc-ROR can regulate cell proliferation, apoptosis, migration, and invasion, it can thus be used as a potential biomarker for patients with tumors and has potential clinical significance as a therapeutic target. This article reviewed the role of linc-ROR in the development of tumors, its related molecular mechanisms, and clinical values.